2014
DOI: 10.1177/0961203314560424
|View full text |Cite
|
Sign up to set email alerts
|

Increased Syk phosphorylation leads to overexpression of TRAF6 in peripheral B cells of patients with systemic lupus erythematosus

Abstract: Our results suggest that the activated Syk-mediated TRAF6 pathway leads to aberrant activation of B cells in SLE, and also highlight Syk as a potential target for B-cell-mediated processes in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…Syk is a positive regulator of TLR signaling (40, 41). Syk activation has been associated with TRAF6 expression in B cells from patients with SLE (38). The association between Syk and TRAF6 suggests an important point of crosstalk in the context of autoimmune disease, suggesting a potential mechanism for how Syk blockade attenuates the TLR9 responses (40).…”
Section: Bcr and Tlr7/tlr9 Signaling Cascades: Crosstalk And Potentiamentioning
confidence: 99%
“…Syk is a positive regulator of TLR signaling (40, 41). Syk activation has been associated with TRAF6 expression in B cells from patients with SLE (38). The association between Syk and TRAF6 suggests an important point of crosstalk in the context of autoimmune disease, suggesting a potential mechanism for how Syk blockade attenuates the TLR9 responses (40).…”
Section: Bcr and Tlr7/tlr9 Signaling Cascades: Crosstalk And Potentiamentioning
confidence: 99%
“…Subsequent studies, recently summarized by Suthers and Sarantopoulos 20 , have identified several potential points of communication between TLR signaling pathways and BCR ITAM signaling. For example, one aspect of TLR–BCR crosstalk involves Syk-driven upregulation of the TLR signaling molecule TRAF6 21 . However, this mechanism requires induction of new gene expression, a process that would take minutes to hours and thus cannot account for receptor synergy that occurs within seconds of receptor engagement.…”
Section: Pre-transcriptional Controlmentioning
confidence: 99%
“…TRAF6 is an E3 ligase which acts as an intermediate signalling adaptor between signals such as pathogen-associated molecular patterns (PAMPs) and downstream pathways including nuclear factor-kB (NF-kb), c-Jun N-terminal kinase (JNK), mitogen-activated protein kinase (MAPK) and AMP-activated protein kinase (AMPK). TRAF6 is involved in immune responses via the regulation of inflammation [ 16 ], differentiation and proliferation of B cells [ 17 ] and development of medullary thymic epithelial cells [ 18 ]. TRAF6 also is implicated in muscle atrophy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%